DETERMINAN JUMLAH PEMBIAYAAN BANK SYARIAH DI INDONESIA - Dyatama, Ayank Narita; Yuliadi, Imamudin (Jurnal Ekonomi & Studi Pembangunan, 2015)
Abstract: The research aims to analyze the factors influencing the distribution of banking credit, that include the third-party fund, Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), and the placing fund in the Seritifikat Bank Indonesia Syariah (SBIS). The data which is used is taken from the financial report of the Conventional Bank and the Shari’a Bank period 2010-2014. The technique analysis used the multiple linear regression model, the hypothesis test with the t-test to determine the variable partially, and f-test to determine all variables at once with the significant of 5 persen. The third party fund has positive influence and significant to the distribution of banking credit Non Performing Loan (NPL) and Return On Assets (ROA) has negative influence and significant to the distribution of credit banking. The placing fund in Sertifikat Bank Indonesia Syariah (SBIS) and Capital Adequacy Ratio (CAR) has negative influence and not significant to the distribution of Shari’a banking financing.Abstrak: Studi ini bertujuan menganalisis faktor-faktor yang mempengaruhi kebijakan penyaluran kredit perbankan, yang meliputi Dana Pihak Ketiga (DPK), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), dan penempatan dana di Sertifikat Bank Indonesia Syariah (SBIS). Data yang digunakan diperoleh dari laporan keuangan Bank Umum dan Bank Syariah pada tahun 2010-2014. Teknik analisis yang digunakan adalah regresi linier berganda, uji hipotesis dengan uji-t untuk menguji variabel secara parsial, dan uji-F untuk menguji variabel secara serempak dengan tingkat signifikansi 5 persen. DPK berpengaruh positif dan signifikan terhadap penyaluran kredit perbankan NPL dan ROA berpengaruh negatif dan signifikan terhadap penyaluran kredit perbankan. Penempatan dana di Sertifikat Bank Indonesia Syariah (SBIS) dan CAR berpengaruh negatif dan tidak signifikan terhadap jumlah penyaluran pembiayaan perbankan syariah.